Design of magnetic-resonant wireless power transfer links realized with two coils: comparison of solutions. Issue 3 (23rd April 2015) - Costanzo, Alessandra; Dionigi, Marco; Mastri, Franco; Mongiardo, Mauro; Russer, Johannes A.; Russer, Peter
Abstract : A novel approach for the rigorous design of magnetic resonant wireless power transfer links is introduced. We show how, starting from two coupled inductors and making use of general network theory, it is possible to derive analytic rules for designing the source and load terminations which provide the maximum power transfer efficiency or maximize the received power. We also show that, by adding suitable matching networks to two coupled inductors we can realize a wireless link acting as a 1:n transformer and having the all required tunable reactive elements on the primary side. The proposed topology greatly simplifies the design, since only an inductive coil and a fixed capacitance are required on the secondary side; in addition, when tuning is required due to coils misalignment or to link distance variation, it can be attained by acting on the transmitter side without the need for a feedback communication through the link. Moreover, when the load resistance is designed for maximum output power, its value is fixed and does not depend on the coupling. A numerical and experimental verification of the proposed approach is also presented.